THE DIFFERENCES OF INTERNATIONAL SHARIAH EQUITY SCREENING PRACTICES - ROHIMAH, INTAN; NURHAYATI, NUNUNG; IHWANUDIN, NANDANG (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This study examines the screening procedures for Sharia-compliant investments used by nine regional and international devisors: AAOIFI, DJIMI, KLSI, FTSE, S&P, MSCI, Al Meezan, JII, and ISSI. The discrepancies between the Shariah-compliant practices and guiding principles of these respectable organizations were highlighted through a comparative study using the most recent data to be obtained. To clearly examine the similarities and differences between the various screening procedures, the business and financial screens were examined independently. While some of these practitioners are more generic and permit more entities to be included, others are more precise and identify forbidden actions under Sharia law. Both a qualitative and a quantitative two-step screening procedure were used by users. The permitted threshold ratio range for impermissible criteria in quantitative screening varies slightly between criteria. There is a common understanding that compliant assets from different nations and practices are acceptable due to the wide range in screening techniques utilized by practitioners. Standardization is thought to be necessary in order to prevent misconceptions between academics and investors regarding what might be halal and what might be haram while screening equities, in addition to aiding investors in comprehending Shariah investment.